Surgical Versus Nonsurgical Lower Face Contouring: Layperson Perceptions of Attractiveness and Personality Traits. Issue 2 (11th March 2022) - Chen, Jonlin; Abousy, Mya; Chow, Amanda; Girard, Alisa; Jenny, Hillary; Choi, Jong-Woo; Yang, Robin
Abstract : Background: Traditional approaches to lower face contouring involve ostectomy of the mandibular angle or body. More recently, nonsurgical techniques have gained popularity, including neurotoxin injection to the masseter muscle. This study aims to evaluate layperson perceptions of patient attractiveness and personality traits following lower face contouring using either surgical or nonsurgical treatment. Methods: In this survey study distributed via Amazon's Mechanical Turk, respondents viewed a series of 14 patient images obtained in clinic before and after surgical or nonsurgical jawline slimming, or without any facial aesthetic procedure. Respondents rated changes in attractiveness and personality trait scores between the before and after image (score: −50 to 50, with 50 representing the greatest posttreatment increase and 0 representing no change). We used descriptive statistics and multivariable regression to determine differences in respondent ratings between patient images. Results: A total of 415 respondents (mean age 38 years, 50.6% female) successfully completed the survey. Compared to patients who underwent nonsurgical treatment, those who received surgery had significantly greater increases in perceived attractiveness ( P < 0.001), femininity ( P < 0.001), friendliness ( P < 0.001), intelligence ( P < 0.001), trustworthiness ( P < 0.001), financial wealthiness ( P < 0.001), dominance ( P < 0.01), and self-esteem ( P < 0.001). Gonial angles increased and jaw widths decreased following both surgical and nonsurgical intervention, with no statistically significant difference between treatment groups. Conclusions: From the layperson perspective, surgical compared to nonsurgical jawline contouring offers greater improvements in perceptions of attractiveness and favorable personality traits.